Територіальний поділ України: чинники інноваційного розвитку та євроінтеграції - Вовканич, С.; Цапок, С. (№3, 2007)
The questions of Ukraine territory division in the context of European and other developed countries, historical Ukrainian experience, optimization of the modern status of territory organization in the system of intensification issues of innovation and eurointegration processes are reviewed as well as preservation of the country sovereignty and title nation identity.